REPRESENTATION OF YOON SUK-YEOL AND LEE JAE-MYUNG IN SOUTH KOREA PRESIDENTIAL ELECTION NEWS - Lia Amelia Nurkhazanah; Nani Darmayanti; Fahmy Lukman (Lire Journal (Journal of Linguistics and Literature), 2022)
This study focuses on examining the representations of Lee Jae-myung and Yoon Suk-yeol contained in the Chosun and Hankyoreh media in terms of the dimensions of the microstructure text based on the theory of critical discourse analysis of Teun A. Van Dijk. The objects of this research are two news stories in the media Chosun and Hankyoreh which report on the first round of the presidential debate in 2022. This study uses a qualitative method with a critical approach. The data collection techniques in this study were documentation, literature study, also reading, listening, and note-taking techniques. The results show that the Chosun and Hankyoreh media have their own tendencies in showing the image of Lee Jae-myung and Yoon Suk-yeol. In Chosun news, there is a tendency to portray the presidential candidate debate that was held on February 3, which tends to portray Lee Jae-myung as a person who is careless in answering questions, while Yoon Seok-yool as a person who is not ready to become a presidential candidate. This is seen from the data that Chosun media based on the content of propositions that explain Lee Jae-myung's weakness amounted to 6 propositions compared to Yoon Seok-yool which only amounted to 2 propositions. Meanwhile, in the Hankyoreh media, the news describing the weaknesses of Lee Jae-myung and Yoon Seok-yool amounted to two propositions. This shows that Hankyoreh is trying to convey the representation of the two candidates in a balanced way. As for the perspective of Van Dijk's discourse theory, it can be concluded that in terms of the dimensions of the microstructure text, there are several elements not found in the news, namely the semantic element - presupposition in the Hankyoreh news. Then, there are no graphic and metaphorical rhetorical elements in the two analyzed news